2016
DOI: 10.1038/srep34983
|View full text |Cite
|
Sign up to set email alerts
|

Moku virus; a new Iflavirus found in wasps, honey bees and Varroa

Abstract: There is an increasing global trend of emerging infectious diseases (EIDs) affecting a wide range of species, including honey bees. The global epidemic of the single stranded RNA Deformed wing virus (DWV), driven by the spread of Varroa destructor has been well documented. However, DWV is just one of many insect RNA viruses which infect a wide range of hosts. Here we report the full genome sequence of a novel Iflavirus named Moku virus (MV), discovered in the social wasp Vespula pensylvanica collected in Hawai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 27 publications
3
73
0
Order By: Relevance
“…In case of the more recently discovered viruses, such as MKV and LhuBLV1, the knowledge of disease symptoms, dynamics, or host range is very limited [36,37]. Studies suggest that the predatory wasp V. pensylvanica may represent an MKV reservoir on Hawaii [16,36]. We confirmed active MKV replication in three different wasp species and an overall high prevalence in Vespinae, supporting the potential virus reservoir.…”
Section: Host Range Of Rna Virusessupporting
confidence: 67%
See 2 more Smart Citations
“…In case of the more recently discovered viruses, such as MKV and LhuBLV1, the knowledge of disease symptoms, dynamics, or host range is very limited [36,37]. Studies suggest that the predatory wasp V. pensylvanica may represent an MKV reservoir on Hawaii [16,36]. We confirmed active MKV replication in three different wasp species and an overall high prevalence in Vespinae, supporting the potential virus reservoir.…”
Section: Host Range Of Rna Virusessupporting
confidence: 67%
“…Samples were screened for four +ssRNA viruses, DWV, BQCV, KBV, and MKV, and an -ssRNA virus, LhuBLV1, using RT-PCR. MKV has only recently been discovered in wasps and bees [36], and LhuBLV1 in Argentine ants [37]. A preliminary screening of a pooled sample for the seven Argentine ant viruses discovered by Viljakainen et al [37] concluded that only the -ssRNA virus LhuBLV1 was hosted by insects other than Argentine ants and was therefore included in the analysis.…”
Section: Rna Extraction and Reverse Transcription Pcr For Virus Detecmentioning
confidence: 99%
See 1 more Smart Citation
“…Apis mellifera is not well adapted to the mite, and infested colonies suffer severe damage (Oldroyd 1999). The damage caused by Varroa to the colonies is not strictly related to the parasitic action of the mite, as it also vectors numerous honey bee viral pathogens, such as deformed wing virus (DWV) (De Miranda and Genersch 2010; Wilfert et al 2016), the member of the iflavirus group, also including slow bee paralysis virus (Kalynych et al 2016), sacbrood virus (Ryabov et al 2016) and Moku virus (Mordecai et al 2016). The Varroa mite, in combination with its associated viruses, most notably DWV, has been associated with the death of millions of European honey bee colonies across the word (Brettell and Martin 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We now recognize a spectrum of microbial pathogens of honey bees, including approximately 20 different RNA viruses, four bacteria, three fungi, and several protozoan parasites [10,1214]. Multicellular parasites and pests further complicate the bee’s ability to sustain the intricate activities of the colony, especially during winter.…”
Section: Introductionmentioning
confidence: 99%